USING LIVE BROADCASTING ON FACEBOOK AMONG JORDANIAN JOURNALISTS - Omar Abdallah Alzoubi, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Journalists' use of live broadcasting on social media platforms has become popular to share news and discuss it with followers. This study aimed to know what the gratifications achieved from the use of the live broadcast feature on Facebook among Jordanian journalists and what are the most posts of journalists in the live broadcast via Facebook, which received great interaction from their viewers. To achieve the study objectives, descriptive research has used by electronic questionnaire. The study sample consisted of (114) journalists using live broadcasting, selected purposely. The results of the study revealed that the use of live broadcasting significantly contributed to increasing journalist skills. On the other hand, Live broadcasting which broadcasts exclusive news ranked first for the most viewed posts.